Content Validity and Interrater Reliability of a Newborn Fall Risk Assessment Tool: KAnt Fall. (4th April 2023) - Savage, Krystal; Antista, Hannah; Diamond, Taylor; Knepp, Alyssa; Oja, Kenneth
Abstract : Background: Newborn falls are a safety concern in the acute care setting. To our knowledge, a valid and reliable tool for assessing newborn fall risk has not been developed. Purpose: To evaluate the content validity and interrater reliability of a tool for nurses to assess the fall risk of newborns in the acute care setting. Methods: Content validity was established using a modified Delphi technique with neonatal intensive care unit (NICU) nurses (n = 27). Item-level content validity indices and an average scale content validity index were calculated. For interrater reliability, pairs (n = 130) of NICU nurses simultaneously assessed multiple newborns using the tool, and an intraclass correlation coefficient was calculated. Results: The initial tool had 28 items classified in 2 sections (newborn and caregiver variables). Fourteen items met predefined cut-off values for content validity. This resulted in the tool (KAnt Fall) having 7 items for assessing newborns and 7 items for caregivers. The intraclass correlation coefficient was 0.99 indicating excellent interrater reliability. Implications for Practice: The tool will help assist nurses in systematically identifying newborns at high risk for falls. This assessment will allow nurses to identify and implement timely preventive actions for hospitalized newborns at high risk for falls. Implications for Research: Since this was a single-center study in 1 NICU, future research is needed in other hospitals and types of newborn settings (eg, labor and delivery and postpartum units). Further testing of KAnt Fall is also needed to establish additional psychometric properties.